Science of human origins - Tuniz, C. (Claudio) (Left Coast Press, 2014)
"Our understanding of human origins has been revolutionized by new discoveries in the past two decades. In this book, three leading paleoanthropologists and physical scientists illuminate, in friendly, accessible language, the amazing findings behind the latest theories. They describe new scientific and technical tools for dating, DNA analysis, remote survey, and paleoenvironmental assessment that enabled recent breakthroughs in research. They also explain the early development of the modern human cortex, the evolution of symbolic language and complex tools, and our strange cousins from Flores and Denisova"--